The Biology, Epidemiology, Host Variability and Management of Sorghum Smut Diseases in Nigeria: A Review - Mustapha, Tijjani; Kutama, A. S; Mai-abba, Ishiyaku Abdullahi; Musa, Hadiza Murtala (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Sorghum Smut diseases in Nigeria are widely circulated and are economically important in most of the regions of the country growing Sorghum. Perhaps, all the four types of smut can co-exist on the same field and are co-extensive with sorghum cultivation. The four smut diseases are incited by four species belonging to two genera of the order ustilaginales, namely; Sporisorium or Sphacelotheca and Tolyposporium. The distribution of the four smut diseases depend on several interacting factors of epidemiology and pathogenesis. It has been reported that all the four species that causes smuts in sorghum have narrow host range. As a consequence therefore, they do not vary remarkably in their biology and pathogenesis. However, their severity, distribution and prevalence depend on the environmental conditions, seasons and variety of sorghum. Several control as well as management strategies have been suggested by workers for the prevention and control of sorghum smuts including the pre-sowing seed treatment using fungicides, the use of resistant plant variety and modification of cultural and handling practices. However, only few of these measures have been found suitable and promising. Moreover, there is scarce of scientific information on the incidence of sorghum smuts probably because they were thought to have been eradicated or that they are economically less important in most sorghum growing areas in Nigeria. But with the current climatic changes coupled with the negligence from the poor resource sorghum farmers, sorghum smut diseases are re-emerging with high threshold as such they are becoming very important in Nigeria’s sorghum growing regions. This paper reviews the epidemiology, biology and variability of smut pathogens and their possible control strategies.